Formation of Creative Activity of Primary School Students with Quilling Techniques - Sanjar qizi, Uralova Muhabbat (European Journal of Life Safety and Stability (2660-9630), 2021)
The article is about the formation of creative activity of primary school students with the help of quilling techniques, the importance of quilling techniques, their role in the life of students. Further improvement of students' interests with the help of quilling techniques and information about the types of quilling.